Mary Poppins [videorecording (Blu-Ray + DVD)] - Andrews, Julie; Stevenson, Robert, 1905-1986; Van Dyke, Dick; Tomlinson, David, 1917-2000; Travers, P. L. (Pamela Lyndon), 1899-1996 (Disney Blu-ray., 2013)
An English nanny with magical abilities takes over the household of a proper London banker and changes the lives of everyone.